Parkinson’s LRRK2-G2019S risk gene mutation drives sex-specific behavioral and cellular adaptations to chronic variable stress - Guevara, Christopher A.; Alloo, Kumayl; Gupta, Swati; Thomas, Romario; del Valle, Pamela; Magee, Alexandra R.; Benson, Deanna L.; Huntley, George W. (Frontiers in Behavioral Neuroscience, 2024)
Anxiety is a psychiatric non-motor symptom of Parkinson's that can appear in the prodromal period. Parkinson'srelated anxiety affects females more than males. How stress, anxiety and Parkinson's are related and the basis for a sex-specific impact of stress in Parkinson's are not clear. We addressed this using young adult male and female mice carrying a G2019S knockin mutation of leucine-rich repeat kinase 2 (Lrrk2 G2019S ) and Lrrk2 WT mice. To assess within-sex differences between genotypes in stress-induced anxiety-like behaviors in young adulthood, we used a within-subject design whereby mice underwent tests of anxiety-like behaviors before and following a 28 day (d) variable stress paradigm. There were no differences in behavioral measures between genotypes in males or females at baseline. Following stress, male G2019S mice were affected similarly to male wildtypes except for novelty-suppressed feeding, where stress had no impact on G2019S mice while significantly increasing latency to feed in Lrrk2 WT control mice. Female Lrrk2 G2019S mice were impacted similarly to wildtype females across all behavioral measures. Post-stress analyses compared cFos immunolabeling-based cellular activity patterns across several stress-relevant brain regions. The density of cFos-activated neurons across brain regions in both male and female Lrrk2 G2019S mice was generally lower compared to stressed Lrrk2 WT mice, except for the nucleus accumbens which in male Lrrk2 G2019S mice, cell density was significantly higher than all other groups. These data suggest that the Lrrk2 G2019S mutation differentially impacts anxiety-like behavioral responses to chronic stress in males and females that may reflect sex-